OFFSET
0,8
COMMENTS
FORMULA
G.f.=G=G(t, z) satisfies G=1+zG(G-1+t-tz+z).
EXAMPLE
T(4,2)=4 because we have uu(ud)(ud)dd, uudd(ud)(ud), (ud)uudd(ud) and
(ud)(ud)uudd (the peaks that are not of the form uudd are shown between parentheses).
Triangle begins:
1;
0,1;
1,0,1;
1,2,1,1;
2,4,4,3,1;
4,9,13,9,6,1
MAPLE
G:=1/2/z*(1-z^2+z-t*z+z^2*t-sqrt(1-z^2+z^4-2*z^3+4*z^3*t-2*z^4*t+t^2*z^2-2*t^2*z^3+z^4*t^2-2*t*z-2*z)): Gser:=simplify(series(G, z=0, 15)): P[0]:=1: for n from 1 to 13 do P[n]:=coeff(Gser, z^n) od: for n from 0 to 13 do seq(coeff(t*P[n], t^k), k=1..n+1) od; # yields sequence in triangular form
CROSSREFS
KEYWORD
nonn,tabl
AUTHOR
Emeric Deutsch, Jun 23 2005
STATUS
approved